2017
DOI: 10.17306/j.afs.0482
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of sucrose and high-fructose corn syrup on lipid metabolism and the risk of cardiovascular disease in male rats

Abstract: Cardiovascular diseases (CVD) are the primary cause of premature deaths, particularly in developing countries. Blood lipid disorders, including low levels of high density lipoprotein cholesterol (HDL-C) and high levels of triacylgycerols (TG) and low density lipoprotein cholesterol (LDL-C), constitute a crucial risk factor for CVD (Yusuf et al., 2004; Weissglas-Volkov and Pajukanta, 2010). The adverse changes in blood lipid parameters may result from excessive consumption of monosaccharides and disaccharides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 0 publications
0
10
0
7
Order By: Relevance
“…The authors hypothesize that this difference is due to discrepancies in the activity of various transaminase enzymes, with increased conversion of fructose to alanine, serine, glycine, and cystine compared to sucrose [ 17 ]. A study by Sadowsk and Bruszdowska comparing sucrose to 55% high-fructose corn syrup (HFCS-55, 55% fructose:45% glucose) in Wistar rats over 6 weeks shows no difference between the two sugar preparations with regard to weight gain or energy intake, but HFCS-55 also increases plasma glucose and triglycerides [ 18 ]. Mock et al found that rats drinking high-fructose corn syrup have the highest level of hepatic de novo lipogenesis and steatosis, and the greatest reduction in β-oxidation, compared to fructose or sucrose sweetened water [ 19 ].…”
Section: Fructose Glucose and Sucrose: Is There Really A Difference?mentioning
confidence: 99%
“…The authors hypothesize that this difference is due to discrepancies in the activity of various transaminase enzymes, with increased conversion of fructose to alanine, serine, glycine, and cystine compared to sucrose [ 17 ]. A study by Sadowsk and Bruszdowska comparing sucrose to 55% high-fructose corn syrup (HFCS-55, 55% fructose:45% glucose) in Wistar rats over 6 weeks shows no difference between the two sugar preparations with regard to weight gain or energy intake, but HFCS-55 also increases plasma glucose and triglycerides [ 18 ]. Mock et al found that rats drinking high-fructose corn syrup have the highest level of hepatic de novo lipogenesis and steatosis, and the greatest reduction in β-oxidation, compared to fructose or sucrose sweetened water [ 19 ].…”
Section: Fructose Glucose and Sucrose: Is There Really A Difference?mentioning
confidence: 99%
“…В некоторых работах отмечается повышение содержания общего ХС в плазме крови, например в диетах, богатых фруктозой или жирами и фруктозой [10,24], или отсутствие изменения его уровня [12]. Сведения относительно ХС-ЛПВП также варьируют, с преобладанием данных об их уменьшении [15]. Рассчитанный AIP у крыс, получавших диету с высоким содержанием жиров и углеводов, увеличивался в 3 раза (0,2 ± 0,1 в контрольной против 0,6 ± 0,2 в опытной группе, р = 0,001).…”
Section: результаты и обсуждениеunclassified
“…В последние годы все большее распространение приобретает комбинированная высокожировая диета с повышенным содержанием углеводов (также именуемая как западная диета, диета кафетерия) [10][11][12]. Показано, что животные жиры (лярд или говяжий жир) в этом случае оказываются более эффективными для моделирования МС по сравнению с растительными жирами [11], тогда как в качестве добавляемых в рацион углеводов можно использовать глюкозу [12], фруктозу [13,14] или сахарозу [15]. Такая диета наиболее приближена к питанию современного человека и считается максимально адекватной для моделирования метаболического синдрома и воспроизведения патогенетических факторов и феноменологии метаболических нарушений при МС.…”
Section: Introductionunclassified
“…High ingestion of fructose, especially in the form of sweetened beverages, has been identified as a serious risk factor for the development of metabolic diseases in adults, as well as in adolescents. Sadowska et al, 2017, in their study showed that the effects of beverages sweetened with HFCS were important in significantly reducing plasma HDL (High Density Lipoproteins) levels. The currently study consists in a literature review that aims to show that early metabolic syndrome found in adolescent who consumed high rich fructose diet; exploring malfunctions in different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using experimental adolescent rats have shown that chronic consumption of fructoserich diet induces systemic metabolic disorders that mimic aspects of the metabolic syndrome in humans, including hypertension, hypertriglyceridemia and hyperinsulinemia (SADOWSKA et al, 2017;WHITE et al, 2008).…”
Section: Introductionmentioning
confidence: 99%